Malignant Peritoneal Mesothelioma Mimicking Ischemic Colitis - Yuusuke Mitsuka; Shintaro Yamazaki; Taiki Miyakuni; Atsuko Iwama; Tomoya Funada; Yoshifumi Watanabe; Teruo Kaiga; Shunji Okada; Mitsugu Kochi; Tadatoshi Takayama (Case Reports in Gastroenterology, 2010)
The prognosis of malignant peritoneal mesothelioma is extremely poor with a mean survival time of 12 months. The initial symptoms are poor and atypical. Because of its rare entity and little knowledge of its treatments, there are few reports of long-term survival. We encountered a very unique case with strong impression on radiological findings of malignant peritoneal methothelioma. We had misdiagnosed it because of the findings and because the time course was similar to that of ischemic colitis. The radiological findings on CT and enema disappeared within one week after antibiotic therapy.